Rossi’s Kitāb al-Sinna: A Seventeenth-Century Note of Tribal Law in Yemen - Paul Dresch (Arabian Humanities)
Several texts on customary, non‑Islamic law have been collected by researchers working in Yemen. Few are accessible, and fewer still have been published. They represent a tradition, or set of traditions, associated particularly with tribal areas of Yemen, that is of some antiquity. It is important to make the material more widely available as a resource not only for those interested in the country’s history but for those concerned with the relation between learned and colloquial forms of law. The present article offers an annotated translation of one such text, collected by Ettore Rossi in the 1930s. The text itself, which was copied for Rossi, is dated 1059/1649, and purports to come from Khawlān al‑Ṭiyyāl.